Textbook News Values: Stable Concepts, Changing Choices. (September 2019) - Parks, Perry
This article examines the historical contingency of news values as evidenced in journalism historiography and more than a century of journalism reporting and writing textbooks dating to 1894. Textbooks are important distillers and (re)constructors of journalists' conceptions of news and not-news. Findings suggest that although key news values such as timeliness, proximity, prominence, unusualness, conflict, human interest, and impact have been fundamentally stable since the early 1900s, the way those values are applied to reporting depends on the sociocultural context of the era. A key implication is that news values are neither natural nor inevitable, but rather within journalists' power to change.